Endgame solving the Iraq crisis - Scott Ritter (New York, NY Simon & Schuster, 1999)
Drawing upon his experiences in Iraq, the former U.N. chief weapons inspector explains where U.S. policy in Iraq went wrong. He details the ways in which Saddam Hussein tried to foil inspectors by concealing his weapons programs; illustrates some of the dramatic face-offs between U.N. inspectors and hostile Iraqi officials; and criticizes the U.S. for squandering opportunities for international consensus and trying to use the inspections process for uniquely American goals
Keywords: Weapons of mass destruction--Iraq.